Hematocele After Laparoscopic Appendectomy - Chaudhary, Sushant (Society of Laparoendoscopic Surgeons, 2012)
BACKGROUND: Laparoscopic appendectomy is one of the most common laparoscopic surgeries performed. We report an unusual complication of hematocele after laparoscopic appendectomy. CASE DESCRIPTION: A 48-y-old male presented with swelling and discomfort in his right scrotum 11 d after he underwent laparoscopic appendectomy for acute appendicitis. Before the surgery, he had no scrotal swelling or inguinal hernia.